A Method to Promote the Development of Intelligence and Game Skills in Youth Football - Giovanni Esposito; Francesca D'Elia; Gaetano Raiola (OVS LLC, 2020)
Research purpose. The aim of the study is to evaluate the playing skills of the young players under investigation in a global context. Specifically, it is intended to test whether the proposed training methodology favorably influenced the development of game skills, increasing the efficiency of game performance. Materials and methods. The study participants are 24 young players, aged between 13 and 14. To achieve the tasks set, the study relied on the following methods: analysis of scientific literature, field testing and methods of mathematical statistics. The experimental group performed a specific training mesocycle (that of the Brain Kinetic), while the control group performed a traditional working mesocycle. To detect the effects of the training methodologies, field tests  were used both before and after the training period, respecting the execution protocols described by H. Wein. The study materials were processed by the statistical analysis software-IBM SPSS 22. A paired sample t-test was used to compare the results of the two groups. Results. The t-test analysis indicates statistically significant changes in the training effect of the experimental group. A better performance index found in the experimental group in the execution of skills, compared to the control group, is due to the diversification of the methodology to which they were subjected. Therefore, the changes after training at each skill index are amplified by the subsequent repetition of the tests. Differences between test indicators are statistically significant (p = 0.25) Conclusions. The study, through the use of field tests, has confirmed the hypothesis that the use of the Brain Kinetic training method determines a positive training effect in skill exercises. This method allowed the players involved in the experimental group to take personal, individual and group actions that had a real impact on the outcome of the game.